Social Media Use and Academic Performance: A Study on Undergraduate Accounting Students in Bangladesh - Khanam, Zobaida (Asian Journal of Accounting Perspectives, 2020)
Research aim: The paper aims to ascertain the relationship between social media uses and academic performance of undergraduate accounting students in Bangladesh. Design/Methodology/Approach: This study is based on empirical data gathered from a survey of 154 undergraduate accounting students in Bangladesh. Structural equation modelling (SEM) analysis is applied to make sense of the results of the research questions. Research findings: The analysis disclosed that five factors are categorised as the reasons for using social media for academic purposes of which online sharing and academic comprehension have a significant positive impact on academic performance (CGPA), whereas the completion of course tasks have a significant negative impact on CGPA or the academic performance. Academic involvement and personal tutorial support do not associate significantly with academic performance (CGPA). Theoretical contribution/ Originality: Most of the studies on social media focus on the relationship between social media use and educational outcome in general, not concentrating on a particular subject. As regards the subject specificity, the interest and satisfaction of learning accounting course was measured through the use of social media. In Bangladesh, the study of social media use is limited. This analysis concentrates particularly on accounting discipline learning perspective. Practitioner/ Policy implication: This study identifies different academic uses of social media and defines policies and procedures that will modify the use of social media as learning tools of undergraduate students. Research limitation: This study considered only 154 undergraduate students in Bangladesh, mainly from the capital city Dhaka. The investigation is limited to the data collected from the survey questionnaire administered to the sampled students. Keywords: Social media use, Accounting students, Academic performance, CGPA Type of Manuscript: Research paper JEL Classification: A22, M41, M49